Answer:A
Step-by-step explanation: this is aquadratic equation and can be solved by using factorisation.
To use factorisation method we need to look for two numbers that when we muliply them we get +1 and when we add them we get -2
So that is -1 and -1
-1*-1=+1
-1+(-1)=-2
so now we substitube -2x with the two known factors which will give us;
x²-1x-1x+1=0
now we factorise this equation. which will give us;
x(x-1)-1(x-1)=0
now we pick the factors outside the bracket and the factors inside the bracket, which will give us;
(x-1)(x-1)=0
so;
x-1=0 and
x-1 =0
take 1 to the other side, which will give us;
x=1 two timesA